Observational study of multiple myeloma in Latin America - Hungria, Vania T. M. (2017)
Relatively little is known about the outcomes of multiple myeloma in Latin America, a world region where incorporation of novel agents is generally slow. In the current retrospective-prospective study, we aimed to describe the patterns of care and treatment results in five Latin American countries. Between April 2007 and October 2009, patients who had been diagnosed from January 2005 to December 2007 were registered at 23 institutions from Argentina, Brazil, Chile, Mexico, and Peru. We divided patients into two cohorts, according to transplantation eligibility, and analyzed them with regard to first-line treatment and overall survival (OS). We analyzed a total of 852 patients, 46.9 % of whom were female. The median follow-up was 62 months. Among transplantation-ineligible patients (N = 461), the mean age was 67.4 years, approximately one third of patients received a thalidomide-based treatment in the first line, and the median OS was 43.0 months. Transplantation-eligible patients (N = 391) had a mean age of 54.7 years and a median OS of 73.6 months. Autologous transplantation was performed in 58.6 % of the patients for whom this procedure was initially planned and in only 26.9 % of the overall patients. Our longterm results reflect the contemporary literature for patients with multiple myeloma treated with autologous transplantation and thalidomide-based regimens in clinical trials and observational studies. However, further efforts are needed to approve and incorporate novel agents in Latin American countries, as well as to increase access to transplantation, in order to achieve the expected improvements in patient outcomes.